The hidden traces: The Prosperity Gospel in Latin America in light of its ideological origins in the New Thought Movement - Quesada Chaves, Marco Antonio (2020)
In the last three decades, Christian groupings have managed to project andinstall themselves gradually in the political structures of several Latin Americancountries, managing to occupy diverse governmental instances in orderto promote their own agendas. Given this phenomenon, it is important tocritically and investigatively address the theological discourse that many ofthese congregations and political parties promote, which is known as theProsperity Gospel. In the present article, a historical survey is carried outto trace what its ideological origins are, one of its main sources being thephilosophical and spiritual movement of the New Thought, which emergedin the mid-nineteenth century in the United States. In this way, a questionarises about whether the Prosperity Gospel is really theology, by discussingand contrasting its main slogans from a theological and critical perspective.